The validity of raw custom-processed global navigation satellite systems data during straight-line sprinting across multiple days - Crang, Z. L.; Duthie, G.; Cole, M. H.; Weakley, J.; Hewitt, A.; Johnston, R. D. (Journal of Science and Medicine in Sport, 2023)
Objectives (1) Determine the validity of instantaneous speed and acceleration and (2) the variation in validity over time (multiple sessions) for global navigation satellite systems (GNSS) devices.